2013
DOI: 10.1002/phy2.23
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and GLP-1 infusions demonstrate the onset of adipose-specific insulin resistance in a large fasting mammal: potential glucogenic role for GLP-1

Abstract: Prolonged food deprivation increases lipid oxidation and utilization, which may contribute to the onset of the insulin resistance associated with fasting. Because insulin resistance promotes the preservation of glucose and oxidation of fat, it has been suggested to be an adaptive response to food deprivation. However, fasting mammals exhibit hypoinsulinemia, suggesting that the insulin resistance-like conditions they experience may actually result from reduced pancreatic sensitivity to glucose/capacity to secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 39 publications
(135 reference statements)
5
48
1
Order By: Relevance
“…It is plausible that elevations in glucose during late breeding might have occurred after the 120-min observation period, but that elevated glucose had not returned to baseline levels by the 48-hour measurement. Prior work in other age classes of elephant seals has demonstrated that the pancreatic release of insulin after a prolonged period of fasting is negligible and that there is an increase in insulin resistance to some tissues [59][60][61]. It is possible that the same trends in the insulin regulation of glucose exist in the adult males subjected to prolonged fasts.…”
mentioning
confidence: 82%
“…It is plausible that elevations in glucose during late breeding might have occurred after the 120-min observation period, but that elevated glucose had not returned to baseline levels by the 48-hour measurement. Prior work in other age classes of elephant seals has demonstrated that the pancreatic release of insulin after a prolonged period of fasting is negligible and that there is an increase in insulin resistance to some tissues [59][60][61]. It is possible that the same trends in the insulin regulation of glucose exist in the adult males subjected to prolonged fasts.…”
mentioning
confidence: 82%
“…Another endocrine response/consequence of food deprivation is the onset of insulin resistance that spares glucose for glucose-dependent tissues such as the central nervous system (28, 42, 48, 52, 53, 131,133). Fasting in humans is associated with a drop in plasma glucose, a drop that is sustained for up to 33 days of fasting, and decreased plasma insulin; a similar response is seen in rats (23, 46, 62).…”
Section: Thyroid Status and Insulin Resistancementioning
confidence: 72%
“…Over the course of their postweaning fast, pups develop adipose-specific insulin resistance associated with an increase in TH production, leading to increased cellular TH-mediated responses (79,82,129,130,132,133). In response to a TSH infusion, both T4 and T3 increased in late-fasted pups.…”
Section: Fasting-adapted Mammals As Natural Models For Human Diseasementioning
confidence: 99%
See 2 more Smart Citations